2015
DOI: 10.2147/ijn.s75023
|View full text |Cite
|
Sign up to set email alerts
|

Chloramphenicol encapsulated in poly-ε-caprolactone–pluronic composite: nanoparticles for treatment of MRSA-infected burn wounds

Abstract: The emergence of methicillin-resistant Staphylococcus aureus (MRSA) infection has increased precipitously over the past several decades, with far-reaching health care and societal costs. MRSA infections in the context of burn wounds lead to invasive disease that could potentially cause mortality. Chloramphenicol is a well-known broad-spectrum bacteriostatic antibiotic that has been used since 1949, but due to its hydrophobicity, poor penetration in skin, fast degradation, and toxicity, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 39 publications
6
36
0
Order By: Relevance
“…If we compare effectiveness of the test nanomaterials, it can be concluded that the most effective against C. lusitaniaе was Chloramphenicol in the nutrient medium in combination withhold: RGO (2:1) followed by Coll: Ag/ SiO 2 /RGO (2:1)>Coll: ZnTiO3 (2:1)>Coll: Ag/ZnO/ZnTiO 3 (2:0.8)>Coll: Ag/RGO (2:0.7). Our results are comparable with these previously reported by other authors [61,62,63,64]. Strongest effect of Coll: Ag/ SiO 2 /RGO nanocomposite without antibiotic in nutrient medium was possibly due to the role of SiO 2 as dispersing agent (vehiculum).…”
Section: Resultssupporting
confidence: 92%
“…If we compare effectiveness of the test nanomaterials, it can be concluded that the most effective against C. lusitaniaе was Chloramphenicol in the nutrient medium in combination withhold: RGO (2:1) followed by Coll: Ag/ SiO 2 /RGO (2:1)>Coll: ZnTiO3 (2:1)>Coll: Ag/ZnO/ZnTiO 3 (2:0.8)>Coll: Ag/RGO (2:0.7). Our results are comparable with these previously reported by other authors [61,62,63,64]. Strongest effect of Coll: Ag/ SiO 2 /RGO nanocomposite without antibiotic in nutrient medium was possibly due to the role of SiO 2 as dispersing agent (vehiculum).…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, these comparable patterns of XRD patterns also demonstrate that the drug molecule was loaded within the nanocarriers. Similar patterns of findings were also observed by other studies 8,21,56,57…”
Section: Resultssupporting
confidence: 92%
“…Tetrazolium salt assay (MTT) was used to determine the cytotoxic concentration of ZJME and ZJWF (Kalita S. et al, 2015, 2016; Kandimalla et al, 2016b; Konwar et al, 2016). Briefly, the cells from the culture flask were trypsinized and seeded in 96-well plate at 5 × 10 3 cells/well in a culture medium and incubated in the CO 2 incubator at 37°C for 24 h. Then the culture medium from the wells was replaced with new media and ZJME and ZJWF at different concentrations (5, 25, 50,125, 250, and 500 μg/mL).…”
Section: Methodsmentioning
confidence: 99%